Selective Collection and Condensation of Exhaled Breath for Glucose Detection - Tankasala, Divya (Conf Proc IEEE Eng Med Biol Soc, 2018)
Exhaled breath condensate (EBC) is a promising non-invasive sample for the detection of various analytes, such as glucose. However, the methods used to collect EBC are highly inconsistent; the variable dilution factors associated with water vapor and the inclusion of dead space air significantly impact the reliability of reported analyte concentrations in EBC. For example, current EBC glucose measurements have resulted in dilution factors ranging from 1/1000 to 1/50000 [1]. There is a need for a systematic and selective EBC collection method to ensure accurate analyte detection and quantification. Herein, we develop and characterize a low-cost, portable condenser which selectively collects exhaled breath that has been exchanged with lung fluid in a temperature-based manner. We demonstrate that for ~15 L of exhaled air, our device can condense reproducible volumes of EBC (>130 µL) in under 3 minutes (p > 0.05, n = 3). Furthermore, our preliminary results indicate that a higher concentration of glucose is detected in the collected sample with selective valve opening (p < 0.05, n = 3). The development of this device enables a repeatable and robust collection method to enable the evaluation of correlations between analytes in EBC and blood.